THE INFLUENCE OF NPF, BOPO, AND CKPN ON THE ROA OF SHARIA BUSINESS UNIT IN INDONESIA - Siregar, Pani Akhiruddin; Wirian, Oktrigana; Ruslan, Muhammad; Afandi, Ahmad; Olivia, Hastuti (Proceeding International Seminar of Islamic Studies, 2024)
This research aims to analyze the influence of NPF, BOPO, and CKPN on the ROA of Sharia Business Unit in Indonesia. The type of research data with secondary data is sourced from the Financial Ratios of Islamic Business Unit and Islamic Business Unit Operations through the publication of The Sharia Indonesia Banking Statistics, Financial Services Authority (SPS-OJK). The SPS-OJK is is a publication media that provides data regarding the Sharia banking industry in Indonesia. The research sample was taken periodically in the form of monthly data from January 2020 to August 2023. At least, the amount of data that can be further analyzed is 44 data. Sampling technique with simple random sampling. The results of the research are as follows: (1) The estimation model shows an R2 value of 0,893 which represents the value of the coefficient of determination. This means that 89,30% of the dependent variable variation is able to be explained by the independent variable in this model. The remaining 10,70% is explained by other causes that are not included in the model; (2) The regression model on the independent variable simultaneously influence the dependent variable, so that the independent variable regression model can be used to predict the dependent variable; and (3) This research produced output that NPF, BOPO, and CKPN have an influential and are significant on the ROA of Sharia Business Unit in Indonesia.